2013
DOI: 10.1097/jnr.0000000000000007
|View full text |Cite
|
Sign up to set email alerts
|

Parental Knowledge, Concerns, and Management of Childhood Fever in Taiwan

Abstract: Participants' lack of fever-related knowledge was because, in part, of either their not understanding or their dissatisfaction with provided information. The higher level of concern compared with other countries and studies indicates that parents in Taiwan need appropriate information about fever management to alleviate their concerns and guide them in caring for their febrile children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
53
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(58 citation statements)
references
References 2 publications
4
53
0
1
Order By: Relevance
“…29 Some studies reported other practices including administering herbal medicine (Taiwan) and tepid sponging (Palestine) which has not earlier been reported extensively from India. 19,22 We found wet sponging as a prevalent practice to control fever among 75% parents while the use of alternative drugs including homeopathic and others was minimal (2%). A study among under-5 children attempted to categorize the childcare practices including fever treatment practices among Indian children as beneficial, harmful or potentially harmless.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…29 Some studies reported other practices including administering herbal medicine (Taiwan) and tepid sponging (Palestine) which has not earlier been reported extensively from India. 19,22 We found wet sponging as a prevalent practice to control fever among 75% parents while the use of alternative drugs including homeopathic and others was minimal (2%). A study among under-5 children attempted to categorize the childcare practices including fever treatment practices among Indian children as beneficial, harmful or potentially harmless.…”
Section: Discussionmentioning
confidence: 85%
“…Antipyretics usage for treatment of childhood fever has been shown to be very common, and knowledge of resulting complications was very less among parents. 22,35 We reported an association between the advising source of antibiotics (other than doctor) and inappropriate fever management practices which reflects the common behavior of the South Indian urban population. Singh et al have shown earlier that Indian parents learn about fever management from other sources including parents and relatives rather than doctors.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…This may be due in part to enduring cultural beliefs and norms and inadequate continuing health literacy among caregivers and care providers. There is thus need for culturally sensitive and competent health literacy interventions to mitigate deleterious impacts of perceptions, perspectives and common practices related to home management of fever in this part of the world [45][46][47][48][49][50][51][52][53].…”
Section: Resultsmentioning
confidence: 99%
“…Parents in Taiwan need information about the management of fever to lessen the anxiety and guide them in performing the fever treatment in children. 20 In table 3, it can be seen the difference in the average score for knowledge, attitudes and actions of parents in intervention group whom provided health education about fever with control group (without education) with p value of each 0.009, 0.03, and 0.002. This suggests that educational interventions can improve knowledge, attitudes and actions of parents in handling fevers in children.…”
Section: Discussionmentioning
confidence: 99%